Prospective Evaluation of Auditory Brainstem Response against Hearing Loss Risk Factrs. A Clinical Based Study - Shahid Majeed, Samina Farooqi, Hafiz Safiullah Khattak, Sajid Rashid Nagra, Kamran Chaudhry, Fayaz Ahmed Memon (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The purpose of this study is to determine the improvement of auditory brainstem response against hearing loss risk factors among new born babies. Study Design: Prospective study Place and Duration: Bahawalpur Medical and Dental College, Bahawalpur and General Hospital, Lahore. Jan, 2021 to June, 2021 Methods: There were one hundred and thirty high risk infants were presented in this study. Birth weight and gestational age as well as transfusion and asphyxiation rates were documented once the parents provided written permission. Included patients had absent ABR or ABR thresholds ≥80 dBnHL. ABR testing during natural or chloral hydrate-induced sleep was part of the audiologist’s examination. Patients with aberrant ABR responses underwent further testing, including optical absorption empiricism (OAE). Measurements of immittance were performed as necessary. All data was analyzed by using SPSS 22.0. Results: Among 130 cases, majority of the infants were males 85 (65.4%) and 45 (34.6%) infants were females. Mean gestational age of the infants was 35.11± 6.42 weeks. Mean weight of the infants was 1899.1± 2.654 grams. Frequency of severe birth asphyxia was seen in 65 (50%) cases. We found exchange transfusion in 25 (19.2%) cases. Improvement in ABR threshold was seen in 70 (53.8%) cases, partial improvement in 27 (20.8%) cases and no improvement was seen in 33 (25.4%) cases. After 3-4 months among patients of no/partial improvement, 42 (70%) patients were improved and no improvement was seen in 18 (30%) cases. Conclusion: We concluded in this study that the hearing loss can be improved in infants by early ear screening by using ABR thresholds. Re-screening of ABR thresholds provided better results among infants. Staged further hearing testing of babies is needed to monitor hearing development at an early age utilizing repeated ABR measures to identify hearing impairment and detect threshold changes crucial for treatment decision-making.